Development of Neutralizing and Non-neutralizing Antibodies Targeting Known and Novel Epitopes of TcdB of Clostridioides difficile - Fühner, Viola; Heine, Philip Alexander; Helmsing, Saskia; Goy, Sebastian; Heidepriem, Jasmin; Loeffler, Felix F.; Dübel, Stefan; Gerhard, Ralf; Hust, Michael (Frontiers in Microbiology, 2018)
Clostridioides difficile is the causative bacterium in 15 – 20 % of all antibiotic associated diarrheas. The symptoms associated with Clostridioides difficile infection (CDI) are primarily induced by the two large exotoxins TcdA and TcdB. Both toxins enter target cells by receptor-mediated endocytosis. Although different toxin receptors have been identified, it is no valid therapeutic option to prevent receptor endocytosis. Therapeutics, such as neutralizing antibodies, directly targeting both toxins are in development. Interestingly, only the anti-TcdB antibody bezlotoxumab but not the anti-TcdA antibody actoxumab prevented recurrence of CDI in clinical trials. In this work, 31 human antibody fragments against TcdB were selected by antibody phage display from the human naive antibody gene libraries HAL9/10. These antibody fragments were further characterized by in vitro neutralization assays. The epitopes of the neutralizing and non-neutralizing antibody fragments were analyzed by domain mapping, TcdB fragment phage display, and peptide arrays, to identify neutralizing and non-neutralizing epitopes. A new neutralizing epitope within the glucosyltransferase domain of TcdB was identified, providing new insights into the relevance of different toxin regions in respect of neutralization and toxicity.